2002
DOI: 10.1197/aemj.9.9.947
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine: Competencies for Youth Violence Prevention and Control

Abstract: By any standard one wishes to apply, the impact of violence on the health and safety of the public is significant. The expression of violence among children in the United States has increased significantly during the modern era. Homicide and suicide are the second and third leading causes of death in youths 15-24 years of age. The emergency department (ED) is a common site for the care of these victims, and because victims often become assailants, the emergency care provider needs to know the epidemiology, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…In fact, several ED‐based interventions have been shown to be effective in this regard 17,18 . Thus, it is important for the pediatric ED care provider to know the epidemiology of youth violence to facilitate the creation and evaluation of prevention programs 19 . To guide these efforts, research priorities for violence prevention in the ED have been elucidated 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several ED‐based interventions have been shown to be effective in this regard 17,18 . Thus, it is important for the pediatric ED care provider to know the epidemiology of youth violence to facilitate the creation and evaluation of prevention programs 19 . To guide these efforts, research priorities for violence prevention in the ED have been elucidated 20 .…”
Section: Discussionmentioning
confidence: 99%
“…They are characterized by their involvement in severe criminal activity [7,8]. Gang violence is an increasing public health problem in the US [7][8][9][10][11]. The Federal Bureau of Investigation [10] reported that there are 1.4 million active gang members in the US.…”
Section: Factors That Influence Youth Gang Membershipmentioning
confidence: 99%
“…1 There are therefore many reasons why surgeons should be involved in helping to understand the causes of violence and in its prevention. The second part of this article addresses ways in which surgeons, can -some may argue,should -be involved in roles other than their clinical one in helping humanity deal with the scourge of violence.Drawing on the seven roles defined by the CanMEDS By collaborating with social services, schools and community groups we can help bring the reality of the harm done by violence to those for whom violence is often just a game.We can participate in violence prevention programmes 6,7 and help individuals and communities break out of cycles of violence,working with networks such as the WHO-sponsored Violence Prevention Alliance,the Violence Reduction Unit (Scotland), or Violent Crime Ta sk Groups (England and Wales). By way of example,Warburton and Shepherd described in 2002 how maxillofacial surgeons were becoming involved in the wider issues of violence prevention.…”
Section: Ann R Coll Surg Englmentioning
confidence: 99%